Anna Akhmatova in the Russian Literary Field (1940s–1960s): Pragmatics and Semantics of the Poetic Dedications to M. A. Bulgakov and E. S. Bulgakova - Михайлова, Галина (Literatūra, 2017)
This article is based on Pierre Bourdieu’s theory of fields, more precisely – on the concept of the literary field. The poetic dedication to Mikhail Bulgakov is considered as one of examples of Anna Akhmatova’s “positions and trajectories” in the Russian literary field. An epitaph to Mikhail Bulgakov, which was included in the poetic cycle A Wreath for the Dead, and the poem Hostess, devoted to Elena Bulgakova, are regarded as certain artifacts the reason and purpose of which were not only in the addressees of dedications. The history of creation and announcement of the epitaphs (in the censored and not censored circumstances) as well as the semantics of these poems show the aspiration of the poet to contribute to the sphere of “cultural production,” which was corrected in the “thaw” years. Akhmatova, as an “agent” of the cultural field, had the considerable “symbolic capital” and sought to take part in the course of a statement of other (not Soviet) regulating norms and the others, the earlier rejected (discriminated) as well as the aesthetic and ethical values in the modern Russian literary field. Certain “movements” of Akhmatova in this direction coincided with the “gestures” of Elena Bulgakova and the other “agents” of the literary field, who moved Mikhail Bulgakov’s personality and works from the periphery of cultural process to its center. ANA ACHMATOVA 1940–1960 mm. RUSŲ LITERATŪROS LAUKE: EILIUOTŲ DEDIKACIJŲ M. A. IR J. S. BULGAKOVAMS PRAGMATIKA IR SEMANTIKA Straipsnis remiasi prancūzų sociologo ir filosofo Pierre’o Bourdieu „laukų“ teorija, tiksliau – „literatūros lauko“ sąvoka. Michailui Bulgakovui dedikuotos Anos Achmatovos eilės nagrinėjamos kaip vienos iš Achmatovos „pozicijų ir trajektorijų“ rusų literatūros lauke. Šios pozicijos koordinatės ir „judėjimai” yra traktuojamas kaip iš anksto apgalvoti poeto veiksmai (gestai). „Epitafija“ Michailui Bulgakovui, įtraukta į poetinį ciklą „Vainikas mirusiems“, kaip ir Jelenai Bulgakovai dedikuotas eilėraštis „Šeimininkė“, įvertinami kaip artefaktai, kurių priežastis ir tikslas – ne tik dedikacijų adresatai. „Epitafijos“ sukūrimo ir paskelbimo istorijos, susiklosčiusios dėl cenzūros ir necenzūros aplinkybių, o taip pat eilėraščio semantika rodo, kad Achmatova siekė įnešti savo dalį į „kultūros produktų gamybos“ sferą, kurį buvo koreguojama „atšilimo“ metais. Achmatova kaip savo laiko kultūros lauko „agentė“, turinti nemažą „simbolinį kapitalą“, siekė dalyvauti kitų (nesovietinių) literatūros lauko reguliavimo normų ir kitų (ankščiau atmestų ir diskriminuotų) estetinių ir etinių vertybių įteisinimo procese. Tam tikri Achmatovos „judesiai“ šia kryptimi sutapo su J. Bulgakovos ir kitų literatūros lauko „agentų“ „gestais“ siekiant perkelti M. Bulgakovo asmenybę ir kūrybą iš kultūrinio proceso periferijos į centrą.